Prevalence of risk factors and 10 year risk estimation of cardiovascular diseases among rural population of Mysuru, Karnataka - Kadiyala, Prathyusha; Renuka, M.; Kulkarni, Praveen; Narayanamurthy, M. R. (International Journal Of Community Medicine And Public Health, 2019)
Background: Cardiovascular diseases (CVD) are leading cause of death among non-communicable diseases (NCD). Many people in developing countries are detected late and die from NCDs, often in their most productive years. Prevention of CVD is an essential step to control the epidemic of NCDs. Thus, this study was undertaken to assess the prevalence of risk factors and to estimate the risk of CVD in the next 10 years. Methods: A community based cross-sectional study was conducted among 608 individuals aged ≥40 years in rural area of Mysuru. Data was collected using Semi structured questionnaire and 10 year CVD risk was estimated using World Health Organization/International Society of Hypertension (WHO/ISH) risk prediction charts. Results: A total of 608 study participants (mean age 56.76±11.07 years; Male:Female ratio 1.2:1) were included in the study. The prevalence of tobacco (32.9%) and alcohol (20.1%) consumption was significantly higher among males compared with females. Hypertension, diabetes and obesity prevalence was 39.5%, 15.5% and 28.1% respectively. One-fifth of population had moderate (20-39%) estimated risk and 7.4% had very high (≥40%) risk of developing CVD event in next 10 years. The estimated high risk (≥30%) of CVD events was statistically higher among individuals who were non-literates, unemployed, physically inactive, middle and above socioeconomic status. Conclusions: In the present study, CVD risk factors and estimated risk of CVD were significantly prevalent in the rural population. The use of simple tools like WHO/ISH risk prediction charts to estimate CVD risk is recommended in low resource settings at Community level, as the benefit of screening outweighs the risk of missing an opportunity to prevent CVD.